Nephritogenicity of antibodies to proteoglycans of the glomerular basement membrane--I. - Makino, H (1986)
We investigated nephritogenic potential of antibodies to heparan sulfate-proteoglycan of glomerular basement membrane. Glomeruli were isolated, basement membranes were prepared, proteoglycans extracted, and purified core protein was obtained. We immunized rabbits with the core protein, IgG fraction prepared from the antisera and specificity of the antibody determined. A single immunoprecipitin line in agar diffusion plate and a single band (approximately 18,000 mol wt) on the immunoblot autoradiograms were visualized. The antibody showed precise reactivity with the glomerular basement membranes. The clearance studies indicated that approximately 75% of the radioiodinated antibody disappeared from circulation within 1 h and 1-2% bound to the kidney. For nephritogenicity experiments, the antibody was intravenously administered into rats and we examined their kidneys at 1 h to 24 d later. A linear immunofluorescence of glomerular basement membranes was observed with rabbit IgG at all times while that of C3 until the 10th day. Early morphologic changes included glomerular infiltration of polymorphonuclear leukocytes with focal exfoliation of endothelium. The leukocytic infiltration subsided by the third day and was followed by progressive thickening of basement membranes, focal mesangial cell proliferation, increase in mesangial matrix, and accumulation of monocytes. Focal knob-like thickening of glomerular basement membrane was observed from the 15th day onward. Regularly-spaced electrondense deposits were seen in the lamina rara interna and externa of glomerular basement membranes and persisted throughout the investigatory period. No significant proteinuria was observed at any stage of the experiment. These findings suggest that the antibodies to the basement membrane heparan sulfate-proteoglycan are nephrotoxic but possess weak nephritogenic potential.